ARTIKEL REVIEW : PENERAPAN WILCOXON DALAM BIDANG KEFARMASIAN - Ahda Ratu Jufrida Hanifa; Devia Regina Hartanti; Seruni Sugiharto Putri; Yohanes Gualbertus Briant Lobo; Ervina Ariyani; Dita Diajeng; Ainul Ghurri; Laily Mita Andriana; Arista Wahyu Ningsih (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Statistical analysis is an analysis to make conclusions related to research, one of which is the Wilcoxon test which is a non-parametric test that does not require normal homogeneous data to prove the effectiveness of a test. In all aspects of pharmaceutical research, statistical tests are not only a method of analysis, but also the foundation that ensures the reliability of the findings obtained. This research aims to provide analysis, evaluation and views on the application of the Wilcoxon test in research in the pharmaceutical field. The method used is meta-analysis of 20 journals in the 2019-2023 period. From the results of the journal review, (it was found that 5 out of 20 journals used the Wilcoxon test as pretest and posttest analysis). The Wilcoxon test is a statistical test that is very important and effective in the pharmaceutical field because it does not require the assumption of normality of data, is able to compare paired or unpaired data, as an ordinal or interval data analysis and is sensitive to differences in ranking so that it is a very important statistical tool in research in the field. pharmacy.